Etika Perencanaan Dalam Perspektif Al-Qur'an - Haryono Hadi Kuswanto, Haryono; Mahmud, Hamidullah (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
This article discusses planning ethics from the perspective of the Koran. Planning ethics in the perspective of the Qur'an is a person's behavior in preparing thorough plans that are in accordance with Islamic law. Islam has called for every individual to be able to plan the activities they will carry out. When preparing plans, you must have ethics. Because it doesn't necessarily mean that what is planned will run smoothly according to plan, but there is a God who plans everything. We should realize that God's plan is the most perfect and good for humans. This research method uses a descriptive qualitative analytical approach, with a library research method (Library Research). The results of this research are that there are several findings in planning ethics in Islam, including: (1) Relying on plans on Allah's will, found in QS. Al-Kahf verse: 23, (2) Trust in Allah SWT, found in QS. At-Thalaq verse: 3 and the 3rd (3) Ridho (Qadha and Qadar are found in QS. Al-Ahzab verse: 38.